ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH SEASONED EQUITY OFFERINGS DI BURSA EFEK JAKARTA - N Agus Sunarjanto (LPPM Universitas Terbuka, 2007)
Seasoned Equity Offering (SEO) is an additional public offering of a company?s shares in order to generate extra financing for business expansion or fulfillment of its liability. Based on Jakarta Stock Exchange data, 11 listed companies conducted SEO during year 2001. However, only 8 companies meet the requirements as samples for this research. In order to evaluate financial and operational variables, this research uses financial statement figures published 2 year prior and after SEO?s. Current ratio (CR), debt to equity ratio (DER) are chosen to represent financial variables, while net profit margin (NPM) and return on investment (ROI) represent operational variables. This research reveals that there was no significant difference in financial performance before and after SEO?s. It happened due to several factors, such as: (1) the fund generated from SEO?s were used to settle matured debts; and (2) foreign currency denominated debts which increased in value during the period of economic crisis